2007
DOI: 10.1007/s10875-007-9117-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Maturing T-Cell-Mediated Immune Response in Patients with Idiopathic Parkinson’s Disease Receiving r-metHuGDNF Via Continuous Intraputaminal Infusion

Abstract: The development of a maturing T-cell-mediated immune response was characterized in Parkinson's disease subjects receiving recombinant human glial-derived neurotrophic factor (r-metHuGDNF) via continuous bilateral intraputaminal infusion. Eighteen of 34 subjects tested positive for anti-r-metHuGDNF-binding antibodies. Four subjects developed neutralizing activity, three of which demonstrated classic immunoglobulin class switching from IgM to IgG. An increase of anti-r-metHuGDNF IgG-binding antibodies correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 36 publications
2
42
1
Order By: Relevance
“…Initial clinical trials involved administering GDNF protein, with mixed results ( Refs 37,38,39,40,41,42). The appearance of GDNF antibodies in some patients (Refs 41, 42) highlighted a need to approach NTF therapy differently.…”
Section: Discussionmentioning
confidence: 99%
“…Initial clinical trials involved administering GDNF protein, with mixed results ( Refs 37,38,39,40,41,42). The appearance of GDNF antibodies in some patients (Refs 41, 42) highlighted a need to approach NTF therapy differently.…”
Section: Discussionmentioning
confidence: 99%
“…GDNF-binding antibodies appeared in the serum of approximately half the subjects, and GDNFneutralizing antibodies developed in a small subset of these same subjects. 85 Finally, the concurrent 6-month toxicity studies found a patchy loss of Purkinje cells in some monkeys on high-dose GDNF (100 g/day). Although there was no toxicity attributable to GDNF in the clinical trials, these findings, added to the lack of efficacy in the randomized clinical trial, led Amgen to discontinue the clinical studies.…”
Section: Intraputaminal Administration Of Gdnfmentioning
confidence: 98%
“…After six months of bilateral intraputaminal infusion of recombinant GDNF, there were no significant differences between the motor scores of the unified Parkinson's disease rating scale (UPDRS) in patients that had received GDNF and in those that had received a placebo. Furthermore, safety concerns were raised, since approximately 10% of the GDNF-treated patients developed antibodies against the peptide, which could potentially counteract the therapeutic benefits [131]. A similar proportion of patients who had participated in the two open-label trials also developed antibodies to GDNF [129,130].…”
Section: Gdnf In Clinical Trialsmentioning
confidence: 99%